2021
DOI: 10.1007/s11356-021-14566-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term discharge of acid mine drainage from abandoned coal mines on soil microorganisms: microbial community structure, interaction patterns, and metabolic functions

Abstract: More than twenty abandoned coal mines in the Yudong River basin of Guizhou Province have discharged acid mine drainage (AMD) for a long time. The revelation of microbial community composition, interaction patterns and metabolic functions can contributes to the ecological remediation of AMD pollution. In this study, reference and contaminated soils were collected along the AMD ow path for high-throughput sequencing. Results showed that the long-term AMD pollution promoted the evolution of γ-Proteobacteria, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…All of the above results can be explained by the response of bacteria and fungi to different types of vegetation blankets (Ren et al, 2018). In this study, the results showed that Proteobacteria, Bacteroidetes, Actinobacteria, and Chloroflexi were the main phyla of soil bacteria in the mining area, and the main phylum among fungi was Ascomycota, consistent with the results of previous studies (Chen et al, 2021). The results indicated that there is some similarity in the distribution of microbial communities in the soil environment in the mining area (Liu et al, 2019), while also showing variability to different degrees (Figure 6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All of the above results can be explained by the response of bacteria and fungi to different types of vegetation blankets (Ren et al, 2018). In this study, the results showed that Proteobacteria, Bacteroidetes, Actinobacteria, and Chloroflexi were the main phyla of soil bacteria in the mining area, and the main phylum among fungi was Ascomycota, consistent with the results of previous studies (Chen et al, 2021). The results indicated that there is some similarity in the distribution of microbial communities in the soil environment in the mining area (Liu et al, 2019), while also showing variability to different degrees (Figure 6).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the main phyla of bacterial network nodes were Proteobacteria, Actinobacteria, Bacteroidetes, Firmicutes, and Nitrospirae, while the main phyla of fungal network nodes were Ascomycota, Chytridiomycota, Basidiomycota, and Mortierellomycota. Most of the nodes of bacteria and fungi in the network analysis map were from the dominant phyla, a result that was consistent with the pattern of most studies (Chen et al, 2021; Jiao et al, 2016). The dominant phylum of bacteria in this study, Proteobacteria, contains a variety of genera associated with nitrogen cycling (Wang, Zhou, et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…64,65 The total number of coal mines in china has decreased from more than 80 000 to around 4700 (by the end of 2020) under the guidance of a series of national policies, which is a good initiative for the protection of the world's natural water resources and environment. 66…”
Section: Resultsmentioning
confidence: 99%
“…64,65 The total number of coal mines in china has decreased from more than 80 000 to around 4700 (by the end of 2020) under the guidance of a series of national policies, which is a good initiative for the protection of the world's natural water resources and environment. 66 While Europe has a long and rich history of mining, there are now signicantly more uncontrolled mines than operational mines across the continent and research and development activities across Europe are wide-ranging. 67 European Union (EU) legislation strongly inuences approaches to mine waste/ water management in Europe.…”
Section: Three Elds Plot Of Prolic Countries Abstract and Journal's...mentioning
confidence: 99%
“…The Lower Permian Liangshan Formation is the main coal-bearing stratum, containing bituminous coal with a thickness of 0.8-1.4 m. The rocks below the coal seam are bauxite and aluminous mudstone containing pyrite agglomerates or nodules, and the overly rocks are giant thick ne crystal tuff, and dense tuff interspersed with mud tuff and dolomitic tuff (Ren 2018). The local average multi-year rainfall is about 1264.7 mm, and a large amount of atmospheric precipitation with high dissolved oxygen in ltrates into the underground coal mining area, which, together with the groundwater rebounded into the abandoned coal mine, makes the underground coal mining area an area where complex physical, chemical and biological reactions of various pollutants occur (Chen et al 2021b). As a result, pyrite in the coal seam and surrounding rocks will be oxidized, constituting a large amount of acid mine drainage over owing from the coal mine portal, which in turn causes environmental pollution of surface water (Fig.…”
Section: Sampling Areamentioning
confidence: 99%